Comparative Analysis of DNA Methyltransferase Gene Family in Fungi: A Focus on Basidiomycota - Huang, Ruirui; Ding, Qiangqiang; Xiang, Yanan; Gu, Tingting; Li, Yi (Frontiers in Plant Science, 2016)
DNA methylation plays a crucial role in the regulation of gene expression in eukaryotes. Mushrooms belonging to the phylum Basidiomycota are highly valued for both nutritional and pharmaceutical uses. A growing number of studies have demonstrated the significance of DNA methylation in the development of plants and animals. However, our understanding of DNA methylation in mushrooms is limited. In this study, we identified and conducted comprehensive analyses on DNA methyltransferases (DNMtases) in representative species from Basidiomycota and Ascomycota, and obtained new insights into their classification and characterization in fungi. Our results revealed that DNMtases in basidiomycetes can be divided into two classes, the Dnmt1 class and the newly defined Rad8 class. We also demonstrated that the fusion event between the characteristic domains of the DNMtases family and Snf2 family in the Rad8 class is fungi-specific, possibly indicating a functional novelty of Rad8 DNMtases in fungi. Additionally, expression profiles of DNMtases in the edible mushroom Pleurotus ostreatus revealed diverse expression patterns in various organs and developmental stages. For example, DNMtase genes displayed higher expression levels in dikaryons than in monokaryons. Consistent with the expression profiles, we found that dikaryons are more susceptible to the DNA methyltransferase inhibitor 5-azacytidine. Taken together, our findings pinpoint an important role of DNA methylation during the growth of mushrooms and provide a foundation for understanding of DNMtases in basidiomycetes.